Correlational Analysis of Academic Performance in General Education Courses During the Digital Learning Space - Terania, Lizette; Dela Cruz, Jonathan Daved (Journal of Interdisciplinary Perspectives, 2024)
The integration of digital learning setups in higher education has revolutionized the educational landscape, necessitating a reevaluation of academic performance in General Education Courses (GECs). This correlational analysis study examines the interconnectedness of student grades across eight GECs during the transition to digital learning environments. By investigating the relationships between GEC subjects, the study sheds light on potential interdisciplinary connections and offers insights into overall academic performance trends. Findings reveal significant correlations between various GECs, highlighting the importance of fostering interdisciplinary learning experiences and promoting critical skills development among students in digital educational contexts. The study underscores the imperative of designing curriculum frameworks that encourage holistic learning experiences, prioritizing the development of communication skills, scientific literacy, and ethical reasoning. Additionally, it emphasizes the need for continuous evaluation and improvement initiatives to enhance the quality of education in digital learning environments. This research contributes to a deeper understanding of academic performance trends in GECs and informs pedagogical practices aimed at preparing students for success in an increasingly complex and interconnected world.